Pengaruh Mindfulness, Work-Life Balance dan Kepuasan Karyawan terhadap Kinerja Karyawan pada Karyawan Pasuruan Industrial Estate Rembang - Muhammad Husen Abdillah; Miftahul Huda; Nur Ajizah (MES Bogor, 2024)
The influence of mindfulness, work-life balance and employee satisfaction has a positive and significant influence on employee performance in Rembang industrial estate company employees. This type of research aims to measure the influence of mindfulness, work-life balance and employee satisfaction on employee performance. This research population used a purposive sampling method which obtained a sample size of 100 respondents. The data analysis method uses multiple linear regression analysis with the help of the IBM SPSS Statistical 25 application. The results of the research show that: 1. The mindfulness variable has a significant effect on employee performance, 2. The work-life balance variable has a significant effect on employee performance, 3. The satisfaction variable employees have a significant effect on employee performance. The results of the T test for the variables mindfulness, work-life balance, employee satisfaction and employee performance were obtained at mindfulness Tcount of (4.712) > Ttable (1.984), (WLB) Tcount of (8.089) > Ttable (1.984), (employee satisfaction) Tcount of (3,063) > from Ttable (1,984) it can be concluded that the variables of mindfulness, work-life balance and employee satisfaction have a significant effect on employee performance at companies in the PIER Pasuruan area.